EFFECT OF OPERATING PARAMETER ON THERMAL CONVERSION OF GASIFICATION OF PONGAMIA PINNATA SHELLS - Susastriawan, Anak Agung Putu (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2012)
Typically, composition of producer gas from biomass gasification are combustible gas (CO, H2, and CH4), and noncombustible gas (CO2 and N2). A composition of combustible gas affects a calorific value of producer gas from biomass gasification. Composition of CO, H2, CH4, CO2 and N2 in producer gas is affected by producer gas flow rate and equivalence ratio. This experimental work aims to study an effect of producer gas flow rate and equivalence ratio on composition and calorific value of producer gas from gasification of Pongamia pinnata shells. Gasification of these shells is carried out in a 20 kWe downdraft wood gasifier. Original conical grate of gasifier reactor has been replaced with smaller diameter to encounter a blocking problem in grate section of reactor. Air flow rate into a gasifier reactor is controlled using different number of air nozzle opening. Globe valve is used to control producer gas flow rate. Sample of producer gas is measured using Gas Chromatograph for different flow rate and air nozzle opening. Calorific value of producer gas is calculated from percentage of combustible gas present in producer gas. Equivalence ratio is a ratio of air/biomass theoretical to ratio of air/biomass actual. Optimum calorific value of producer gas from Pongamia pinnata shells gasification is obtained at producer gas flow rate of 9.9 g/s and at equivalence ratio of 0.5.